Fabrication of Ag modified SiO2 electrospun nanofibrous membranes as ultrasensitive and high stable SERS substrates for multiple analytes detection - Wan, Menghui; Zhao, Haodong; Wang, Zhihua; Zou, Xueyan; Zhao, Yanbao; Sun, Lei (Colloid and interface science communications, 2021)
Surface-enhanced Raman spectroscopy (SERS) is a powerful analytical tool, but how to obtain effective and versatile SERS substrates is still a challenge. Herein, a simple and efficient strategy to prepare SERS substrates with ultra-sensitivity, high stability and wide applicability is presented. SiO2 nanofibrous membranes were prepared by electrospinning and calcination, and modified with Ag nanoparticles. The results show that Ag nanoparticles decorated on SiO2 nanofibers evenly and tightly through chemical bonding. The as-prepared membranes exhibit high flexibility and thermostability. The electrospun nanofibrous membranes show an ultra-high sensitivity of 10−11 mol/L (an enhancement factor of 107) for small molecules, and the lowest detection limit near to 10−8 mol/L for pesticides thiram. It is also demonstrated that the substrates remain excellent SERS signal stability even after standing for 60 days (intensity decrease only for 21.7%). More importantly, the as-prepared substrates can be performed for quantitative detection of bacteria. [Display omitted] •SiO2 nanofibrous membranes were prepared through electrospinning and calcination.•SiO2 nanofibers were modified with Ag nanoparticles tightly through chemical bonding.•The membranes exhibit ultrahigh SERS sensitivity for small molecules and pesticide.•The substrates show excellent SERS signal stability in durability test.•It also can be performed for qualitative and quantitative detection of bacteria.